The Oral-Microbiome-Brain Axis and Neuropsychiatric Disorders: An Anthropological Perspective - Bowland, Grace B.; Weyrich, Laura S. (Frontiers in Psychiatry, 2022)
In the 21st century, neuropsychiatric disorders (NPDs) are on the rise, yet the causal mechanisms behind this global epidemic remain poorly understood. A key to these unknowns may lie within the vast communities of bacteria, fungi, and viruses in the body (microbiota), which are intimately linked with health and disease. NPDs were recently shown to be connected to gut microbiota, which can communicate with and influence the brain through the Gut-Brain-Axis (GBA). Parallel studies examining oral microbiota and their connections to the brain also suggest that microbes in the mouth can similarly influence NPD outcomes. However, the mechanisms and pathways that illuminate how oral microbiota and brain communicate in NPDs remain unknown. Here, we review identified mechanisms and pathways that oral microbiota use to engage the brain, and we lay the theoretical foundation for an oral-microbiota-brain axis (OMBA). Specifically, we examine established neuroinflammatory and immune system activation responses that underpin interactions between the oral microbiota and the Central Nervous System (CNS), detailing four specific mechanisms: 1) microbial and metabolite escape, 2) neuroinflammation, 3) CNS signaling, and 4) response to neurohormones. We then scrutinize why including the OMBA, in addition to the GBA, is critically needed to elucidate specific causal relationships between microbial dysbiosis and observed NPD development and progression. Furthermore, we argue for comprehensive, interdisciplinary approaches that integrate lab-based microbiome research and population-level studies that examine the OMBA to improve NPDs. We specifically identify key anthropological perspectives that integrate sociocultural, epidemiological, genetic, and environmental factors that shape the oral microbiome and its interactions with NPDs. Together, future studies of the OMBA in conjunction with interdisciplinary approaches can be used to identify NPD risks and improve outcomes, as well as develop novel intervention and treatment strategies.